Arthroscopic Repair of Articular Surface Partial-Thickness Rotator Cuff Tears: Transtendon Technique versus Repair after Completion of the Tear—A Meta-Analysis - Yohei Ono; Jarret M. Woodmass; Aaron J. Bois; Richard S. Boorman; Gail M. Thornton; Ian K. Y. Lo (Advances in Orthopedics)
Articular surface partial-thickness rotator cuff tears (PTRCTs) are commonly repaired using two different surgical techniques: transtendon repair or repair after completion of the tear. Although a number of studies have demonstrated excellent clinical outcomes, it is unclear which technique may provide superior clinical outcomes and tendon healing. The purpose was to evaluate and compare the clinical outcomes following arthroscopic repair of articular surface PTRCT using a transtendon technique or completion of the tear. A systematic review of the literature was performed following PRISMA guidelines and checklist. The objective outcome measures evaluated in this study were the Constant Score, American Shoulder and Elbow Surgeons score, Visual Analogue Scale, physical examination, and complications. Three studies met our criteria. All were prospective randomized comparative studies with level II evidence and published from 2012 to 2013. A total of 182 shoulders (mean age 53.7 years; mean follow-up 40.5 months) were analyzed as part of this study. Both procedures provided excellent clinical outcomes with no significant difference in Constant Score and other measures between the procedures. Both procedures demonstrated improved clinical outcomes. However, there were no significant differences between each technique. Further studies are required to determine the long-term outcome of each technique.